Mobile Assisted Language Learning: Practices and Readiness in EFL Speaking Class - Ihda Rosdiana; Anin Eka Sulistyawati (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2019)
This research aims to find out the students' readiness of using Mobile Assisted Language Learning (MALL) in EFL speaking class. MALL is viewed as potentially significant method to language learning (Cheon et al, 2012). Furthermore, the strong connection between millennial and technology affects how they want to be taught in higher education. Various researchers also suggest that oral communication skills can be successfully done by mobile phone capabilities. The data of this study were collected through questionnaires to evaluate the psychological readiness of students. The findings showed that the students have positive attitude toward MALL. All the students have smartphone to support the educational purposes inside and outside classroom. Nevertheless, lecturers need to be aware of the background and technological skills of the learners before embedding MALL into speaking class.Â Keywords: mobile assisted language learning, readiness, speaking, higher education